Tropospheric propagation effects at GPS observations in Venezuela - Gustavo Acuña; Melvin Hoyer; Eugen Wildermann (Revista Técnica de la Facultad de Ingeniería, 2011)
Some principal aspects of modelling tropospheric refraction effects on GPS signal propagation are considered using data from three high quality measu ring campaigns in Venezuela under clifferent meteorological. instrumental and observational conditions. GPS data from CASA'93. SIRGAS'95 y the geoid traverse around Maracaibo Lake have been processed by BERNESE v3.4 software using different meteorological modelling. The influence of tropospheric model selection, meteorological pararneters. troposphertc zenith residual factor estimation . observation sesions, cut off angle, etc,. have been studied resulting at coordinate changes from rnilimeters to centimeters at baselines ranging between 50 and 880 kilometers with height changes between 14 y 3500 metters.